Upaya pencegahan terjadinya perdarahan dan syok pada pasien dhf di rsud pandan arang boyolali - DARYANI, SHINTA INTAN DESKY, Siti Arifah, S.Kp., M.Kes (2016)
Background :Faver Haemoragic Dengue (DHF) is a disease caused by dengue virus is transmitted through the bite of Aedes aegypti mosquito that can cause death. Platelets are expected to have an important role in the pathogenesis, based on the fact that in DHF thrombocytopenia accompanied by increased capillary permeability.Clinical manifestations of dengue virus infection is most feared is the occurrence of bleeding and shock are marked with a positive tourniquet test, thrombocytopenia, hemoconcentration resulting in death. Therefore, an accurate assessment of the risk of shock is essential to the management of the edekuat in preventing shock and bleeding. Efforts should be made to prevent the occurrence of bleeding and shock in patients with DHF is to monitor vital signs, laboratory values monitor, assess whether there is bleeding in patients, limit patient activity, advise drinking plenty of mineral water, in collaboration with a team of physicians in the delivery of analgesics. General purpose : writing a scientific paper is to describe efforts to prevent the occurrence of bleeding and shock in patients with DHF (Dengue Haemoragic faver). Specific Objectives : writing scientific papers are analyzing assessment, analyzing intervention and analyze the implementation of the risk of bleeding and shock in patients with DHF. Methods: Scientific paper was prepared using case studies will be undertaken in one patient with DHF Edelweiss Kids wards in hospitals Pandan Arang Boyolali. Sources from the case study authors wrote that from An.W patient, the patient's family, ward nurses and the patient's status. The data collected by interviewing the patients, interviews with the patient's family, the status of the patient and through books and journals.